Long-term outcomes of 176 patients with X-linked hyper-IgM syndrome treated with or without hematopoietic cell transplantation - de la Morena, M. Teresa; Leonard, David; Torgerson, Troy R.; Cabral-Marques, Otavio; Slatter, Mary; Aghamohammadi, Asghar; Chandra, Sharat; Murguia-Favela, Luis; Bonilla, Francisco A.; Kanariou, Maria; Damrongwatanasuk, Rongras; Kuo, Caroline Y.; et al. (Journal of allergy and clinical immunology, 2017)
X-linked hyper-IgM syndrome (XHIGM) is a primary immunodeficiency with high morbidity and mortality compared with those seen in healthy subjects. Hematopoietic cell transplantation (HCT) has been considered a curative therapy, but the procedure has inherent complications and might not be available for all patients. We sought to collect data on the clinical presentation, treatment, and follow-up of a large sample of patients with XHIGM to (1) compare long-term overall survival and general well-being of patients treated with or without HCT along with clinical factors associated with mortality and (2) summarize clinical practice and risk factors in the subgroup of patients treated with HCT. Physicians caring for patients with primary immunodeficiency diseases were identified through the Jeffrey Modell Foundation, United States Immunodeficiency Network, Latin American Society for Immunodeficiency, and Primary Immune Deficiency Treatment Consortium. Data were collected with a Research Electronic Data Capture Web application. Survival from time of diagnosis or transplantation was estimated by using the Kaplan-Meier method compared with log-rank tests and modeled by using proportional hazards regression. Twenty-eight clinical sites provided data on 189 patients given a diagnosis of XHIGM between 1964 and 2013; 176 had valid follow-up and vital status information. Sixty-seven (38%) patients received HCT. The average follow-up time was 8.5 ± 7.2 years (range, 0.1-36.2 years). No difference in overall survival was observed between patients treated with or without HCT (P = .671). However, risk associated with HCT decreased for diagnosis years 1987-1995; the hazard ratio was significantly less than 1 for diagnosis years 1995-1999. Liver disease was a significant predictor of overall survival (hazard ratio, 4.9; 95% confidence limits, 2.2-10.8; P < .001). Among survivors, those treated with HCT had higher median Karnofsky/Lansky scores than those treated without HCT (P < .001). Among patients receiving HCT, 27 (40%) had graft-versus-host disease, and most deaths occurred within 1 year of transplantation. No difference in survival was observed between patients treated with or without HCT across all diagnosis years (1964-2013). However, survivors treated with HCT experienced somewhat greater well-being, and hazards associated with HCT decreased, reaching levels of significantly less risk in the late 1990s. Among patients treated with HCT, treatment at an early age is associated with improved survival. Optimism remains guarded as additional evidence accumulates.